Design and implementation of an electronic lexicon for Modern Greek. - Gakis, Panagiotis; Panagiotakopoulos, Christos; Sgarbas, Kyriakos; Tsalidis, Christos (Literary & Linguistic Computing, 2012)
Natural language text analysis presupposes the encoding of morphological phenomena. In this article, we present some particularities of Modern Greek and the way these are encoded in the presented electronic lexicon. The project plan of its development combined both simple planning algorithms and more elaborate ones for the generation and recognition processes. The resulted lexicon exhibits fast access to its contents and easy content management. It is re-usable and modular enough to support existing NLP applications.